Social Contexts of Phonological Contrasts and Indexicality: Variability and Identity among Singkils - Suhery, D; Hasnain, S I (KnE Social Sciences, 2018)
This paper makes an attempt to look at the relationship between linguistics variation and identity in Singkil, an Austronesian language spoken by the aboriginal speakers living dominantly in five districts namely Kuta Baharu,Simpang Kanan, Suro, Gunung Meriah and Singkil, which are administratively under Singkil regency of Aceh province, Indonesia. According to Ethnologue, Singkil is a dialect of Batak Alas-Kluet (btz). Variation displayed at all levels of language structure ranging from syntax to finegained features of pronunciation, provides one of the defining features of human language. Differences in variation may result from biological given, e.g. differences in laryngeal analogy and physiology among men, women and children causing different levels of fundamental frequency. Differences in variation may also arise on account of social patterning of behavior acquired as a result of a speaker’s regional socio-cultural and language background. These alternatives are consciously noticed by listeners and invariably used by speakers as a source of identity markers. Singkil speakers use these phonetic forms as marker and identity when they interact with other Singkil speakers, it can be seen clearly from the use of phoneme /f/ and /r/. The phoneme /f/ changes to [